2007
DOI: 10.7863/jum.2007.26.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Tumor Vascularity in Benign and Malignant Solid Thyroid Nodules

Abstract: Our study indicates that in small thyroid nodules, quantitative analysis of tumor vascularity has benefits over visual inspection and can be useful in differentiation between benign and malignant thyroid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 15 publications
2
51
0
2
Order By: Relevance
“…In contrast, other studies have reported that certain characteristics on Doppler US including vascular pattern, resistive index (RI) and maximal systolic velocity (MSV) are not useful parameters for distinguishing malignant from benign solid nodules (24)(25)(26). These characteristics, therefore, should not be used as diagnostic tools to determine which nodules should undergo FNAB (27).…”
Section: Thyroid Ultrasonographymentioning
confidence: 87%
“…In contrast, other studies have reported that certain characteristics on Doppler US including vascular pattern, resistive index (RI) and maximal systolic velocity (MSV) are not useful parameters for distinguishing malignant from benign solid nodules (24)(25)(26). These characteristics, therefore, should not be used as diagnostic tools to determine which nodules should undergo FNAB (27).…”
Section: Thyroid Ultrasonographymentioning
confidence: 87%
“…Subjects with simple goiter, non-autoimmune thyroid blood flow, but remains highly subjective and is not sufficient enough to evaluate subtle variations of thyroid vascularity. Several techniques for semi-quantitative measurements of intrathyroidal blood flow have been applied for the differentiation of painless thyroiditis from Graves' disease (10), and benign from malignant thyroid nodules (11). Similar techniques have been used for measurements of thyroid vascularity in healthy subjects (12), and in patients with subacute thyroiditis (13).…”
Section: Subjects Selectionmentioning
confidence: 99%
“…Additionally, other studies have shown that malignant nodules are more likely to have internal vascularity while benign nodules are more likely to have peripheral vascularity (17,21,25). Further analysis is necessary to determine if specific patterns and types of internal or peripheral vascularity are associated with various thyroid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Brunese et al (20) explained that this is due to psammoma bodies, which are around collections of calcifications commonly found in tumors such as papillary thyroid cancer. Others suggest that smaller nodules with vascularity are better predictors of malignancy (21). Further analysis of other suspicious features of malignancy alone and in conjunction with one another is necessary to determine if they may be more accurate predictors of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation